Fragrance and frequencies: EEG analysis of theta spectral edge frequency after olfactory stimulation by spearmint. - Esaba Sadia; Rezvi Ahmed; Md Shaiful Islam Patwary; Israt Jahan (Central Medical College Journal, 2024)
Background: Sense of smell plays a crucial role in emotions, memories, and cognitive processes. The interplay between olfaction and neural activity has intrigued researchers for decades. The signals pass through the olfactory bulb to emotional centers, impacting emotions and memory recall and influencing brain function beyond fragrance identification. Fragrant oils have gained modern attention for their potential to influence cognitive and emotional states. The oil of spearmint is celebrated for its refreshing and calming properties, has emerged as a significant contender in in this context. Objectives: To investigate real-time changes in theta wave Spectral Edge Frequencies (SEF) in response to spearmint fragrance, aiming to understand the dynamic interplay between fragrance and brainwave frequencies. Materials and Methods: Thirty healthy females were exposed to the fragrance of spearmint essential oil, and their brain wave activities were monitored in five brain regions. The recordings were analyzed before and after smelling the fragrance. Wilcoxon Matched-pairs signed Rank test was considered for comparison. Results: Our findings suggest that the olfactory stimulation of spearmint did not exhibit significant influence on the SEF theta waves in any brain regions except in the parietal region. Only this region showed significant shift of theta SEF to a higher frequency after smelling the fragrance compared to baseline (p=0.04). Conclusion: The study revealed no noteworthy alterations in spectral edge frequencies of theta waves in brain regions linked to cognition, memory, or emotions. So, further exploration is recommended, especially in different demographic groups including other waves. Central Medical College Journal Vol 7 No 2 July 2023 Page: 92-96